Determination of the surface morphology of gold-decahedra nanoparticles using an off-axis electron holography dual-lens imaging system - Cantu-Valle, J. (2013)
The purpose of this paper is to show surface irregularities in gold decahedra nanoparticles extracted by using off-axis electron holography in a JEOL ARM 200F microscope. Electron holography has been used in a dual-lens system within the objective lenses: main objective lens and objective minilens. Parameters such as biprism voltage, fringe spacing (σ), fringe width (W) and optimum fringe contrast have been calibrated. The reliability of the transmission electron microscope performance with these parameters was carried out through a plug-in in the Digital-Micrograph software, which considers the mean inner potential within the particle leading a precise determination of the morphological surface of decahedral nanoparticles obtained from the reconstructed unwrapped phase and image processing. We have also shown that electron holography has the capability to extract information from nanoparticle shape that is currently impossible to obtain with any other electron microscopy technique.